2019
DOI: 10.3171/2018.4.jns172644
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the kinetics of sodium fluorescein for fluorescence-guided surgery of glioma

Abstract: OBJECTIVE The use of the optical contrast agent sodium fluorescein (NaFl) to guide resection of gliomas has been under investigation for decades. Although this imaging strategy assumes the agent remains confined to the vasculature except in regions of blood-brain barrier (BBB) disruption, clinical studies have reported significant NaFl signal in normal brain tissue, limiting tumor-to-normal contrast. A possible explanation arises from earlier studies, which reported that NaFl exists in both pure and protein-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…In a recent study, we reported on a comprehensive examination of the kinetics of NaFl in blood, normal brain, and tumor. 15 Specifically, we found that NaFl, which is a relatively small molecule (400 Da) binds only weakly to blood proteins, with a large component remaining in the free state. 15 This unbound NaFl crosses the blood brain barrier while the protein-bound dye remains in the blood.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a recent study, we reported on a comprehensive examination of the kinetics of NaFl in blood, normal brain, and tumor. 15 Specifically, we found that NaFl, which is a relatively small molecule (400 Da) binds only weakly to blood proteins, with a large component remaining in the free state. 15 This unbound NaFl crosses the blood brain barrier while the protein-bound dye remains in the blood.…”
Section: Introductionmentioning
confidence: 85%
“…15 Specifically, we found that NaFl, which is a relatively small molecule (400 Da) binds only weakly to blood proteins, with a large component remaining in the free state. 15 This unbound NaFl crosses the blood brain barrier while the protein-bound dye remains in the blood. This behavior confounds tumor imaging as the unbound dye in the brain reduces the potential tumor-to-normal contrast.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Unspecific leakage of unbound FLS through a heterogeneous and dynamic BBB/BBTB explains reports of unspecific FLS staining in peritumoral areas (238). Compared to unbound FLS, a PEGylated form of FLS with a molecular weight similar to that of gadolinium-based contrast agents (939 Da) showed improved specificity of accumulation in U251 orthotopic mouse gliomas 1 h after administration (95). An albumin-bound formulation of 5-aminofluorescein (66,950 Da) was investigated in a Phase I/II study in Germany (96,97), where bright fluorescence was observed in 10 of 10 patients with high-grade gliomas 0.5 to 4 days after IV administration.…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…Increasing the dose of FLS (5 vs. 20 mg/kg human equivalent) results in an increase in unbound FLS in the blood and normal brain tissue (95). Therefore, the dose and timing of FLS administration should be considered to optimize fluorescent contrast during surgery.…”
Section: Optimal Fls Timing and Dosagementioning
confidence: 99%